Pemanfaatan Pohon Aren (Arrenga pinnata Merr.) oleh Masyarakat Sekitar Hutan Desa Sambaliwali Kabupaten Polewali Mandar - Intan, Nur; Faradilah Farid Karim; Irundu, Daud (Program Studi Kehutanan Fakultas Pertanian dan Kehutanan Universitas Sulawesi Barat, 2023)
Sugar palm plants (Arrenga pinnata Merr) are one of the leading commodities in West Sulawesi. This plant is widely used, both as a household appliance and as a food ingredient for home industry. Sambaliwali Village has the potential to develop sugar palm plants because there are many sugar palm plants that grow naturally. Even though cultivation efforts have not yet been made, people have long used sugar palm as a source of income. The aim of this research is to find out how sugar palm is utilized by the community around the Sambaliwali Village forest. The research method is descriptive qualitative with data analysis techniques according to Miles and Hubberman. The sample was determined using purposive random sampling with 38 sugar palm farmers as respondents from Sambaliwali Village. The results of the research show that the people of Sambaliwali Village process palm sap and palm leaves. Palm sap is made into molding sugar and liquid sugar, while palm leaves to be made into broom sticks. Palm sap processing still uses traditional methods. There has been no effort to cultivate palm plants, until now people have only cultivated sugar palm which grows naturally in the surrounding forest area. Key words: Sugar palm, palm sap, use of forest products